Mary Todd Lincoln papers - Lincoln, Mary Todd, 1818-1882.
Chiefly outgoing correspondence of Mary Todd Lincoln pertaining to the loss of her son, William Wallace Lincoln, and her husband, Abraham Lincoln; the United States Soldiers' Home; travels abroad; and family life. Correspondents include Schuyler Colfax, Jesse Kilgore Dubois, Fanny Campbell Eames, Bertha A. Flatley, Anson G. Henry, Abraham Lincoln, Noyes W. Miner, Sally Orne, John Fox Potter, Caleb B. Smith, Julia Ann Sprigg, A.R. Thompson, A. Wakeman, and Victoria, Queen of Great Britain.
In part, positive and negative photocopies and typewritten transcripts.
Wife of President Abraham Lincoln.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Colfax, Schuyler, -- 1823-1885 -- Correspondence; Dubois, Jesse Kilgore, -- 1811-1876 -- Correspondence; Eames, Fanny Campbell, -- -1890 -- Correspondence; Flatley, Bertha A. -- Correspondence; Henry, Anson G., -- 1804-1865 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865 -- Death and burial; Lincoln, Abraham, -- 1809-1865 -- Correspondence; Lincoln, William Wallace, -- 1850-1862 -- Death and burial; Miner, Noyes W. -- Correspondence; Orne, Sally -- Correspondence; Potter, John Fox, -- 1817-1899 -- Correspondence; Smith, Caleb B. -- 1808-1864 -- Correspondence; Sprigg, Julia Ann -- Correspondence; Thompson, A. R. -- Correspondence; Victoria, -- Queen of Great Britain, -- 1819-1901 -- Correspondence; Wakeman, Abram, -- 1824-1889 -- Correspondence; Lincoln family; United States Soldiers' Home; Voyages and travels; Presidents' spouses -- United States